2014
DOI: 10.1113/jphysiol.2014.277681
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5‐hydroxymethyl‐2‐furfural on the volume and membrane permeability of red blood cells from patients with sickle cell disease

Abstract: Key pointsr We addressed the hypothesis that the heterocyclic aldehyde 5-hydroxymethyl-2-furfural (5HMF) may act synergistically to ameliorate the complications of sickle cell disease through effects on red blood cell (RBC) membrane transport, in addition to its well-known action of increasing the oxygen affinity of the abnormal form of haemoglobin, HbS.r 5HMF was found to reduce deoxygenation-induced dehydration of RBCs, whether in response to maintained deoxygenation or cyclical deoxygenation/re-oxygenation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 50 publications
1
19
0
Order By: Relevance
“…Similar effects on cation transport and RBC hydration have been observed previously with the heterocyclic aldehyde 5HMF (Hannemann et al. ).…”
Section: Discussionsupporting
confidence: 85%
“…Similar effects on cation transport and RBC hydration have been observed previously with the heterocyclic aldehyde 5HMF (Hannemann et al. ).…”
Section: Discussionsupporting
confidence: 85%
“…In vitro 5-HMF reduces sickling-induced dehydration (Gardos and P sickle ) while it increases K loss and dehydration mediated by the K-Cl cotransport [83]. A phase 1 clinical trial tested oral doses of AES-103 up to 4,000 mg in 18 patients with SCD, some treated with hydroxyurea, with no significant side effects [84].…”
Section: Major Therapeutic Strategies For Sickle Cell Diseasementioning
confidence: 99%
“…119 Reduction in P sickle -mediated Ca 2+ by 5-HMF following erythrocyte sickling has also been observed suggesting that this agent may also have an additional anti-sickling effect by inhibiting the deleterious sequelae of Gardos channel activation. 120 Single doses of 5-HMF were well tolerated in a Phase I study, and showed changes in blood oxygen levels during a hypoxia challenge test consistent with the effects of a left-shifting allosteric hemoglobin modifier. 121 This agent is completing Phase II trials in SCD sponsored by AesRx, LLC, and is expected to enter Phase III trials late in 2015 with sponsorship by Baxter.…”
Section: Polymerization Inhibitorsmentioning
confidence: 99%